AB1186 Dynamic contrast enhanced mr imaging in early stage knee osteoarthritis: a test-retest repeatability study in healthy and moderately diseased subjects. (12th June 2018) - Sanaei Nezhad, F.; MacKay, J.; Kaggie, J.; Graves, M.; Gilbert, F.; McCaskie, A.; Flynn, H.; Roberts, C.; Janiczek, R.; Morgan, A.R.; Parker, G.J.
Abstract : Background: Osteoarthritis(OA)in the knee exhibits signs of synovial activation in early phase of disease(. 1 DCE-MRI provides quantitative measurement of vascular disruption associated with synovitis( 2, 3 and has been shown to be sensitive to early treatment-induced changes in small group sizes in multicentre trials(. 4 Objectives: 1 . Determine the reproducibility of DCE-MRI parameters in the knee. 2 . Compare DCE-MRI parameters between participants with mild/moderate OA and aged matched controls. 3 . Enable effect and sample size calculations for further studies. Methods: 9 knee OA patients and 4 controls underwent two MRI scans with a month separation. All patients had diagnosis of knee OA as per ACR criteria, with medial compartment predominant disease and Kellgren-Lawrence grade 2/3 on radiographs. 3 pre-contrast injection series were obtained with flip angles 2 o, 6 o and 14 o for T1 calculation.35 consecutive phases formed the DCE-MRI series(temporal resolution:14 s). Contrast agent(CA)(Dotarem(0.4 mL/kg))was administrated on the 6th phase at the rate 3 mL/s followed by 50 mL saline. All Images were registered together. Here 2 DCE paramaters are reported: K trans (min -1 ), volume transfer constant for CA between blood plasma and extravascular extracellular space; estimated using the extended Tofts model( 5 with population arterial function(; 6 and IAUC60 (mM.s), initial area under CA concentration curve over 60 s post-arrival. Manual segmentation was performed by radiologist. Results: Test-retest coefficient of variation(CoV) was lower in controls. K trans had CoVs of 26/16% in OA patients/controls. An effect size of 30% reduction in K trans (, 4 indicates a treatment effect would be observed in a group of 11 patients with 90% power. DCE parameters were generally higher in OA patients than in controls. 4 out of 9 patients (All with KL score 3)demonstrated parameter values outside the healthy volunteer range at p<0.01 level (one sample t-test). Conclusions: Higher K trans and IAUC60 in patients indicates the potential of revealing microvascular function differences. The fact that this is not observed in all patients could suggest phenotypical variation. High CoV values in patient relative to healthy may be explained in part by fluctuation in disease status. Manual delineation also contributes to this variation. DCE-MRI measures of vascular disruption associated with synovitis in knee OA are practical and feasible for imaging trials. These measures offer greater insight and sensitivity into the inflammatory component of OA that is not captured using other radiological methods. References: [1] Roemer, et al. Osteoarthr Cartil.2010;1269–74. [2] Wenham, et al. Osteoarthr Cartil.2014; 1614–18. [3] Gait, et al. Osteoarthr. Cartil2016;1392–8. [4] Waterton, et al. Eu. Rad2017;3662–8. [5] Tofts, et al. JMRI.1999;223–32. [6] Parker, et al MRM2006:993–1000. Acknowledgements: National Institute for Health Research Cambridge Biomedical Research Centre. Funding provided by GlaxoSmithKline. Disclosure of Interest: None declared